2022
DOI: 10.1002/cjas.1674
|View full text |Cite
|
Sign up to set email alerts
|

The performance of international small and medium‐sized enterprises: Overview and future research directions

Abstract: Our study aims to assess the state of knowledge on the performance of international small and medium‐sized (SME) firms, and formulate a relevant research agenda. We review 231 contributions published between 1993 and 2019, and identify the main theoretical debates, key success factors and measures of international SME performance, and the theoretical and methodological approaches used in this literature. Based on our analysis, we propose a definition of performance factors according to the theoretical framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 235 publications
0
1
0
Order By: Relevance
“…The best cost strategy emphasizes the competence of the company; thus, its competitiveness is very high. In addition, the number of competitors and substitute goods also is tiny [55]. These three strategies have their respective areas of excellence, so no provision solely determines which strategy is the best of all, because it depends on the type of business or product type, market share, and various other factors.…”
Section: Generic Competitive Strategy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The best cost strategy emphasizes the competence of the company; thus, its competitiveness is very high. In addition, the number of competitors and substitute goods also is tiny [55]. These three strategies have their respective areas of excellence, so no provision solely determines which strategy is the best of all, because it depends on the type of business or product type, market share, and various other factors.…”
Section: Generic Competitive Strategy Modelmentioning
confidence: 99%
“…Business strategies differ from strategy at the corporate level. At the business level, this strategy focuses more on improving the competitive position of the company's products or services in certain market segments [55].…”
Section: Business Strategies With Business Performancementioning
confidence: 99%
“…The intricate and challenging startup procedures, combined with the inherent risks of establishing new business ventures, make the lack of entrepreneurial experience a major obstacle for individuals aiming to turn their business ideas into functioning businesses (Lamb et al, 2022;Schulze and Dada, 2024). Entrepreneurship education has evolved to be a distinctive pedagogy that focuses on not only the establishment of new companies but also the theory and practice behind the behaviors of stakeholders in the startup ecosystem, such as entrepreneurs, investors, governments and the market.…”
Section: Entrepreneurship Education and Entrepreneurial Intentionsmentioning
confidence: 99%
“…Furthermore, they found that market-oriented organizations have a stronger connection between innovation and competitive advantage, demonstrating the importance of innovation for adjusting to changing customer desires and preferences. According to Lamb et al (2022), competitive advantage partially mediates the link between innovation and performance by being a positive predictor of both firm performance and innovation capabilities.…”
Section: Performancementioning
confidence: 99%